Q: What does y stand for in 7y 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The 'answer' is the number that 'y' must be if the statement is true.5 + 7y = 11 + 9ySubtract 7y from each side of the equation:5 = 11 + 2ySubtract 11 from each side:-6 = 2yDivide each side by 2 :-3 = y

If you mean: (2x-7y)(x+y) then it is 2x squared -5xy -7y squared

y^2 + 7y + 12 = (y+4)(y+3)

y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2

It's a linear equation in 'y'.You can solve it like this:4y + 2 + 7y = 1Combine the 'y' terms on the left side:11y + 2 = 1Subtract 2 from each side:11y = -1Divide each side by 11:y = -1/11

Related questions

The 'answer' is the number that 'y' must be if the statement is true.5 + 7y = 11 + 9ySubtract 7y from each side of the equation:5 = 11 + 2ySubtract 11 from each side:-6 = 2yDivide each side by 2 :-3 = y

x+7y=16 ---------------------------1 3x- 7y=4 ---------------------------2 ------------------------------------------------------------------------------------------------------------------ 1+2 x+7y=16 3x-7y=4 4x=20 x=5 substitute x = 5 in x+7y=16 (5)+7y=16 7y=11 y=11/7

Points: (7, 0) and (0, 11) Slope: 0-11/7-0 = -11/7 Equation: y-0 = -11/7(x-7) => 7y = -11x+77 Equation: y-11 = -11/7(x-0) => 7y = -11x+77

y=-9 7y-2=14y+61 7y-2-7y=14y+61-7y -2=7y+61 -2-61=7y+61-61 -63=7y -63/7=7y/7 -9=y

Yx7y = 7y2 (squared )

If you mean: (2x-7y)(x+y) then it is 2x squared -5xy -7y squared

y^2 + 7y + 12 = (y+4)(y+3)

x + 7y = 7 ⇒ 7y = -x + 7 ⇒ y = -x/7 + 1 ⇒ y intercept is 1.

Solve the equations by moving the variable to one side : 7y + 11 = 3y + 25 (subtract 3y from each side) 4y + 11 = 25 (subtract 11 from each side) 4y = 14 Y = 3.5

y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2

Let's explain with an example: 2x - 7y = 11 5x + 7y = 3 To solve this system of equations by elimination we "add" the second equation to the first equation. So basically: 2x + 5x - 7y + 7y = 11 + 3 Which then symplifies to: 7x = 14 and x = 2 Then plug x = 2 into the original equation: 5(2) + 7y = 3 Which leads to: y = -1 So the solution is (2,-1).

It's a linear equation in 'y'.You can solve it like this:4y + 2 + 7y = 1Combine the 'y' terms on the left side:11y + 2 = 1Subtract 2 from each side:11y = -1Divide each side by 11:y = -1/11